Study of Ship Resistance due to Trim using Computational Fluid Dynamics - Muhammad Anjas Syam; Baso, Suandar; Ardianti, Andi (Naval Architecture Departement, Hasanuddin University, 2023)
When a ship experiences trim, the geometric parameters of the underwater ship change compared with even keel condition, such as the ship's draft, length of waterline, and wetted surface area. All these factors affect the ship resistance. The purpose of this research is to understand the influence of trim on ship resistance, and to explain the comparison of ship resistance in even keel, trim by bow, and trim by stern conditions based on Computational Fluid Dynamics analysis.. The method for calculating resistance in this research applies software Autodesk CFD. The type of ship in this study is a container ship. In this study, the hydrodynamic analysis of the ship has been successfully conducted, dynamic parameters such as velocity magnitude, static pressure distribution and resistance have been obtained. The ship model's resistance trim by bow and trim by stern conditions shows a similar tendency, increasing with the trim value. However, when comparing the ship model resistance from each trim condition with the resistance in the even keel condition, there is a difference. The trim by bow condition experiences an increase with an average percentage value of 3.32%. Meanwhile, the trim by stern condition experiences a decrease with an average percentage value of 0.06%. Then, overall, trim by bow condition of -1.441 m shows the highest resistance at 6.044 N and trim by stern condition at 0.5 m has the smallest resistance, which is 5.674 N.